Modified low-dose second window indocyanine green technique improves near-infrared fluorescence image-guided dermatofibrosarcoma protuberans resection: A randomized control trial - Cui, Lei; Wang, Gao F.; Li, Xin; Song, Yu Q.; Pu, Wen W.; Zhang, De K.; Jiang, Wei Q.; Kou, Ya Q.; Tan, Zhao Q.; Tao, Ran; Han, Yan; Han, Yu D. (Frontiers in Surgery, 2022)
Objective Conventional second window indocyanine green (SWIG) technique has been widely attempted in near-infrared fluorescence (NIRF) imaging for intraoperative navigation of tumor radical resection. Nevertheless, the overuse of indocyanine green (ICG) led to an increased risk of drug lethal allergy and high medical cost. This prospective study was to explore clinical application of modified low-dose SWIG technique in guiding dermatofibrosarcoma protuberans (DFSPs) radical resection. Method Patients with DFSPs were randomly assigned to control and experimental group. The ICG was injected intravenously 24 hours before surgery, at a dose of 3.5 mg/kg in the control group and 25 mg/patient in the experiment group, respectively. Intraoperative NIRF imaging included serial views of gross tumor, tumor bed and cross-sectional specimen. Results Although NIRF imaging of gross tumor and tumor bed in the experimental group demonstrated similar sensitivity and negative predictive value, the specificity and positive predictive value were obviously higher compared to control group. The tumor-to-background ratios of cross-sectional specimens in the experimental group was significantly higher than in the control group (P=0.000). Data in both groups displayed that there was a positive correlation of tumor size in cross-sections between integrated histopathologic photomicrographs and NIRF imaging of specimen views (P = 0.000). NIRF imaging of cross-sectional specimens had a significant decrease in time cost, and an increase in the ability of examining more surgical margins (P = 0.000). Conclusion This is the first study to demonstrate that a low-dose SWIG technique could improve the accuracy of near-infrared fluorescence image-guided dermatofibrosarcoma protuberans resection.